2003
DOI: 10.1029/2003jc001816
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal discharge of estuarine freshwater to the western Chukchi Sea shelf identified in stable isotope profiles of mollusk shells

Abstract: [1] Oxygen and carbon isotope profiles of bivalve mollusks (Serripes groenlandicus and Macoma calcarea) record distinct changes of water mass properties in the Bering Strait region associated with the seasonal discharge of estuarine freshwater from Kolyuchin Bay into the western Chukchi Sea. Cycles in the d 13C values in these specimens suggests that the properties of the ambient water masses are reflected in the stable isotope profiles. These results show that the stable isotope profiles of mollusk shells ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
5
38
0
1
Order By: Relevance
“…The low freshwater endmember value reflects a contribution of halocline waters imported from the Arctic (Alkire, 2010). composition for all the species studied here (e.g., Wassenaar et al, 1988;Khim, 2002;Khim et al, 2003 Although this relationship was originally derived for sponges, it has been successfully applied to hydrographic reconstructions for Arctic regions using data obtained from shells of A. borealis, S. groenlandicus, and Macoma calcarea from Holocene to modern times (Müller-Lupp et al, 2004;Simstich et al, 2005). On the basis of the strong correlation between the δ 18 o water and salinity shown in Figure 3, we rewrite the above equation as:…”
Section: Bivalve Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The low freshwater endmember value reflects a contribution of halocline waters imported from the Arctic (Alkire, 2010). composition for all the species studied here (e.g., Wassenaar et al, 1988;Khim, 2002;Khim et al, 2003 Although this relationship was originally derived for sponges, it has been successfully applied to hydrographic reconstructions for Arctic regions using data obtained from shells of A. borealis, S. groenlandicus, and Macoma calcarea from Holocene to modern times (Müller-Lupp et al, 2004;Simstich et al, 2005). On the basis of the strong correlation between the δ 18 o water and salinity shown in Figure 3, we rewrite the above equation as:…”
Section: Bivalve Datamentioning
confidence: 99%
“…The use of isotopic data from their shells is gaining significant attention as a valuable tool to generate a much-needed retrospective time series of hydrographic data (Khim et al, 2001(Khim et al, , 2003Müller-Lupp et al, 2003Dettman et al, 2004;Simstich et al, 2005). These organisms accrete calcium carbonate at the ventral margin of their shells throughout the growing period, and this accretion is accentuated in the spring and summer.…”
mentioning
confidence: 99%
“…The latter was suggested to be inflow from the Pacific Ocean through the Bering Strait, based on the high nutrient concentrations, specifically phosphate. Khim et al (2003) used δ 18 O and δ 13 C to deduce the distribution of freshwater in the water column and terrestrial OM in the sediment. They concluded that the runoff signal could be traced more than 50 km off shore even in the end of summer, about 2 month after the peak river discharge.…”
Section: Introductionmentioning
confidence: 99%
“…By improving our understanding of processes, time-series data from a shore-based observatory could have the added advantage of providing insight into shortterm observations made elsewhere in the Arctic. For example, a detailed oxygen isotope composition record for the water column could be used throughout the ice-growing season to provide a basis for understanding the annual variability in the oxygen isotope composition of bicarbonate in bivalves that record isotope ratios (e.g., Khim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%